2008
DOI: 10.1021/ic801450m
|View full text |Cite
|
Sign up to set email alerts
|

The Hydrothermal and Structural Chemistry of Oxovanadium−Arylphosphonate Networks and Frameworks

Abstract: The hydrothermal reactions of NH4VO3 with the aromatic phosphonate ligands 1,4-, 1,3-, and 1,2-phenylenediphosphonic acids (H4L1, H4L3, H4L4, respectively); biphenyl-4,4'-diyldiphosphonic acid (H4L2); and 1,3,5-tris(phenyl)-4,4'-triphosphonic acid (H6L5) yielded materials of the V(x)O(y)/organophosphonate family [VO(H2L1)] (1), [VO(H2L2)] (2), [V2O2(H2O)2(L3)] x 1.5 H2O (3 x 1.5 H2O), [V2O2(H2O)2(L4)] x 2 H2O (4 x 2 H2O), and [V3O3(OH)(H3L5)2] x 7.5 H2O (6 x 7.5 H2O). The reactions were carried out in the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(38 citation statements)
references
References 71 publications
1
37
0
Order By: Relevance
“…Compound 2 was obtained when soluble NH 4 VO 3 was replaced by insoluble V 2 O 5 , having structure similar to reported vanadium phosphates [27]. [37][38][39][40][41].…”
Section: Description Of Crystal Structuresmentioning
confidence: 52%
See 1 more Smart Citation
“…Compound 2 was obtained when soluble NH 4 VO 3 was replaced by insoluble V 2 O 5 , having structure similar to reported vanadium phosphates [27]. [37][38][39][40][41].…”
Section: Description Of Crystal Structuresmentioning
confidence: 52%
“…Many variables influence the construction of the structure, such as the nature of the precursors, pH, temperature, stoichiometries, fill volume, time, autogenous pressure, and the interaction of the organic and the inorganic part [16]. Though vast numbers of vanadium phosphates have been reported, most of them possess infinite structures including one-dimensional (1D) [17][18][19], two-dimensional (2D) [20][21][22][23], and threedimensional (3D) [24][25][26][27][28], whereas only a few examples are discrete [29][30][31]. In this work, we successfully synthesized two new discrete vanadium phosphates (NH 4 ) 5 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, the oxovanadium diphosphonates of the type [V 2 O 2 (H 2 O) x {O 3 P(CH 2 ) n PO 3 }]ÁxH 2 O exhibit three structure types depending on the tether length n [17]. Similarly, the structures of the oxovanadates of the aromatic diphosphonates are quite distinct from those of their aliphatic counterparts [18]. Structural variations are also observed for the oxomolybdateorganodiphosphonate structures [19].…”
Section: Introductionmentioning
confidence: 99%
“…[16]. Since we had previously demonstrated that aromatic diphosphonate ligands provided dramatically different structures than a,x-alkyldiphosphonates in the V x O y -diphosphonate system [17,18] Compound 1 was isolated as bright blue crystals from the hydrothermal reaction of Cu(CH 3 CO 2 ) 2 ÁH 2 O, 2,2 0 -bipyridine, p-xylene diphosphonic acid, MoO 3 and HF in water at 200°C for 2 days [19]. Hydrothermal reaction conditions have been demonstrated to be effective for the synthesis and crystallization of organic-inorganic oxide materials [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%